Severe eosinophilic fasciitis: Comparison of treatment with D-penicillamine plus corticosteroids versus corticosteroids alone - Mendoza, Fabian A. (Scand J Rheumatol, 2015)
OBJECTIVES: To compare the therapeutic effectiveness of corticosteroids (CS) alone versus CS plus D-penicillamine (D-Pen) in severe eosinophilic fasciitis. METHODS: Long term prospective non-randomized trial of D-Pen plus CS vs. CS alone in patients with severe eosinophilic fasciitis, defined as clinically apparent cutaneous fibrotic involvement affecting greater than 15% body surface area (BSA), or greater than 10% BSA with joint flexion contractures. RESULTS: Sixteen patients with severe eosinophilic fasciitis entered the study. Ten patients received D-Pen plus CS and 6 CS alone. Affected BSA decreased from an average of 29% to 8.9% in the D-Pen plus CS group compared to a decrease in affected BSA from 28% to 22.83% in the CS alone group. The reduction in affected BSA in the D-Pen plus CS group was significantly greater than in the CS alone group (p= 0.038). Clinical improvement occurred in all D-Pen plus CS patients, compared to only 33.3% of CS alone patients (p=0.008). There was no difference in overall adverse events frequency between the groups (p=0.60). The most common adverse event in the D-Pen plus CS group was proteinuria (33.3%). However, proteinuria also occurred in 16.6% in the CS-alone group. CONCLUSIONS: Treatment with CS alone failed to induce clinical improvement in the majority of the severe eosinophilic fasciitis patients. In contrast, D-Pen plus CS resulted in significantly greater clinical improvement. These results suggest that initial treatment of severe eosinophilic fasciitis with CS alone is not sufficient for optimal therapeutic response and that addition of an antifibrotic agent results in an improved outcome.